Is it fair tax burden in Colombia (2015)
This essay analyzes the Colombian tax system which is characterized by Permanent changes that generate instability to the tax payers, complexity to its interpretation and inequality in its distribution. Taking into account the need for fiscal resources to meet the public expenditure, Colombian Congress and successive governments have adopted more than ten tax reforms since 1990; a comprehensive transformation is required in order to unify, consolidate and simplify the tax regime, promoting equity, without affecting significantly the tax revenue, and thus contribute to reducing informality, evasion and elution of taxes, increasing competitiveness, creating a more dynamic behavior of investment, employment and hence economic growth of the country. Over time in Colombia, incentives and exemptions have benefited the called large taxpayers who are classified as tax collectors but do not contribute in the same way of their ability to pay. In brief, this investigation concludes that economic inequality in Colombia is caused by preferential tax treatment; therefore tax reforms are characterized by the prominence of the market as allocator of resources, administrative inefficiency, increased government spending that ultimately is what taxpayers demand due to the fact that taxes are not reflected in the welfare of the people